Hubungan Antara Pengetahuan dan Paritas Ibu dengan Perawatan Luka Perineum di Bidan Praktik Mandiri Ratna Wilis Palembang Tahun 2018 - Risa Devita; Aspera Aspera (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2019)
Perineal care procedure by postpartum mothers is very important in preventing infection. Perineal care procedure can be done by applying ice pack compress, applying topical medications such as antiseptic fluid and performing kegel’s exercise. Perineal wound care procedure can be conducted when bathing, after urination and after defacation. The purpose of this research was to find out the correlation between mothers’ knowledge and parity and perineal care procedure in Independent Midwifery Practice (BPM) Ratna Wilis Palembang in 2018.Design research used surveyanalitik method with cross sectionalapproach, the samples of this research were taken by using accidental sampling method as many as 32 postpartum mothers who were hospitalized or mothes who came for a visit during their puerperium period to Independen Midwifery Practice (BPM) Ratna Wilis Palembang in 2018. The research was conducted from November 2018 – January 2019. The data were analyzed by using chi-square test with significance level 95% and (0,05).The results of chi-square test showed the value of mothers’ knowledge variable with ( and the value of mothers’ parity variable with ( which indicated that statistically was a correlation between mothers’ knowledge and parity with perineal care procedure in Independent Midwifery Practice (BPM) Ratna Wilis Palembang in 2018.Recommendedthat the health personnel in Independent Midwifery Parctice Ratna Wilis Palembang socialize about the perineal care procedure to increase mothers’ knowledge of importance of perineal care procedure.